THE PSYCHOLOGICAL AND PHYSICAL EFFECTS OF JAPANESE ANIMATION ON TEENAGERS: A STUDY ON SARGODHA CITY TEENAGERS (Contemporary Journal of Social Science Review, 2025)
This study examines how Japanese animation, or anime, affects teenagers at the University of Sargodha on a psychological and physical level. The study uses a quantitative survey to evaluate the effects of anime on social behavior, physical health, and emotional well-being in a sample of 300 students of Sargodha city. According to the research, anime can have both beneficial and detrimental consequences, even though it also offers entertainment and a way to decompress. While longer anime viewing is linked to physical discomfort like eye strain and irregular sleep patterns, more anime exposure is linked to changes in social behavior and affects on self-perception. This study highlights the need of consuming media with awareness and advances our understanding of anime's complex impact on young people. Among the suggestions are raising awareness of the importance of screen time balance and the potential of anime as a teaching tool.